Analysis on how hotel leaders be role model to staff - Euodia Charity Didimustanto; Nor Afrida Aulia; Izza Ulumuddin Ahmad Asshofi (Journal of Gastro Tourism, 2023)
This Journal reviews the meaning of Hospitality role models in the figure of a leader. When people hear the word role model they often thought about celebrities or famous historical figure. Little did they know that for some people, their role model is their closest friend, work partner, or even family members. What makes a leader is seen as a role model? Someone who can influence people around them and give them great examples are seen as leaders. A leader must have strong values in them self, they have to be confident in leading people who are still lost or still didn’t know the reason why they are here and what are they for. If a leader is not confident of themself then how will they assure people to be confident and overcome their fear such as insecurities and the fear of failling. A leader shall lead them cause when they are under your supervisory, you are responsible for their actions at some circumstances. A leader has to set a good example all the time for the staff, because staff tend to copy what their role model do. This journal will use qualitative method, by getting reference as a research source. This journal will discuss about how to be a great leader and a role model, how to be more than just someone who rule over people and tells people what to do but to be someone who is admired and is set as an example for others especially to staffs. To give example and description on how to be a great leader is what a leader should do. In conclusion every leader should position themselves not as someone who have a high position and just rule over people, they need to be someone who can make staff comfortable and respect them not just as a leader but also as a role model. Guiding them as if their success is your responsibility is a great mindset a hotel leader should have.